2020
DOI: 10.3390/ph13100283
|View full text |Cite
|
Sign up to set email alerts
|

Citrus hystrix Extracts Protect Human Neuronal Cells against High Glucose-Induced Senescence

Abstract: Citrus hystrix (CH) is a beneficial plant utilized in traditional folk medicine to relieve various health ailments. The antisenescent mechanisms of CH extracts were investigated using human neuroblastoma cells (SH-SY5Y). Phytochemical contents and antioxidant activities of CH extracts were analyzed using a gas chromatograph–mass spectrometer (GC-MS), 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) assay and 2,2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) assay. Effects of CH extracts on high gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 119 publications
1
19
0
Order By: Relevance
“…GC-MS/MS analysis of MC extract was performed with the facility available at the Scientific and Technological Research Equipment Center (STREC), Chulalongkorn University, Thailand, according to the standard procedure [ 16 ]. The mass spectra obtained were correlated with the database from NIST2011 Mass Spectrometry Data Center for the identification of phytoconstituents.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…GC-MS/MS analysis of MC extract was performed with the facility available at the Scientific and Technological Research Equipment Center (STREC), Chulalongkorn University, Thailand, according to the standard procedure [ 16 ]. The mass spectra obtained were correlated with the database from NIST2011 Mass Spectrometry Data Center for the identification of phytoconstituents.…”
Section: Methodsmentioning
confidence: 99%
“…Cells (5 × 10 3 cells) were treated or co-treated with MC and phenanthrene (Phe) for 48 h. ROS levels were measured, according to the protocol described elsewhere [ 16 ], and the fluorescence was measured using an EnSpire Plate Reader (Perkin-Elmer) with excitation/emission wavelengths of 485/535 nm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plants have often been used to improve cognitive functions and retain the mental ability for centuries. Recent studies from our lab have reported the neuroprotective efficacies of various plant extracts, including Kaempferia parviflora, Cleistocalyx nervosum, Bacopa monnieri, and Citrus hystrix against toxic insults in cellular and nematode models [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%